Analisis Kualitas Aset Fasilitas Koridor Jalan sebagai Ruang Publik - Fadila, Dela; Angestiwi, Tiafahmi (RUAS, 2023)
Braga Street is a commercial area consisting of road corridors and pedestrian paths. Ideally, optimally functioning public spaces have the best quality so that they have the carrying capacity of community activities. Increasing the activities of urban communities creates many ideas, collaborations, and businesses that support economic growth. To realize the effectiveness of public space, facility assets in public space are the main factor that affects the quality of public space. Evaluation of facility assets on Jalan Braga, Bandung is needed to assess the quality of its assets. The evaluation was carried out using the Public Space Quality Index (PSQI) method. The quality of facility assets is assessed based on aspects of accessibility, maintenance, attractiveness, comfort, safety and security. From the evaluation results, accessibility aspects are categorized as quality class A (highest), maintenance aspects are quality class B (high), attractiveness aspects are categorized as quality class A (highest), comfort aspects are categorized as quality class B (high), and safety and security aspects are categorized as quality class B (high). Overall, Jalan Braga's facility assets are categorized as quality class B (high).